Load-bearing capacity and fracture behavior of glass fiber-reinforced composite cranioplasty implants - Jaakko M. Piitulainen; Riina Mattila; Niko Moritz; Pekka K. Vallittu (WICHTIG PUBLISHING, 2025)
Background: Glass fiber-reinforced composites (FRCs) have been adapted for routine clinical use in various dental restorations and are presently also used in cranial implants. The aim of this study was to measure the load-bearing capacity and failure type of glass FRC implants during static loading with and without interconnective bars and with different fixation modes.Methods: Load-bearing capacities of 2 types of FRC implants with 4 different fixation modes were experimentally tested. The sandwich-like FRC implants were made of 2 sheets of woven FRC fabric, which consisted of silanized, woven E-glass fiber fabrics impregnated in BisGMA-TEGDMA monomer resin matrix. The space between the outer and inner surfaces was filled with glass particles. All FRC implants were tested up to a 10-mm deflection with load-bearing capacity determined at 6-mm deflection. The experimental groups were compared using non-parametric Kruskal-Wallis analysis with Steel-Dwass post hoc test.Results: FRC implants underwent elastic and plastic deformation until 6-mm deflection. The loading test did not demonstrate any protrusions of glass fibers or cut fiber even at 10-mm deflection. An elastic and plastic deformation of the implant occurred until the FRC sheets were separated from each other. In the cases of the freestanding setup (no fixation) and the fixation with 6 screws, the FRC implants with 2 interconnective bars showed a significantly higher load-bearing capacity compared with the implant without interconnective bars.Conclusions: FRC implants used in this study showed a load-bearing capacity which may provide protection for the brain after cranial bone defect reconstruction.